Trade policy options for Sub-Saharan Africa: TTIP, EPAs, WTO and African integration - Evita Schmieg (Stiftung Wissenschaft und Politik (SWP), 2015)
Within the framework of a sustainable foreign trade policy, exports and imports represent a potentially important factor supporting economic and social development. The international level has proposed many objectives and instruments to harness that potential for the benefit of developing countries. Yet sub-Saharan Africa's exports are still overwhelmingly unprocessed raw materials that make little contribution to value added and development. Decades of EU (and to some extent also US) trade preferences have produced little in the way of practical impacts for these countries, talks at the World Trade Organisation have progressed at snail's pace, and the promised development dividend has failed to materialise. Implementation of the Transatlantic Trade and Investment Partnership will further sharpen the pressure of competition. Economic Partnership Agreements concluded with the European Union bring risks as well as opportunities. What possibilities do countries south of the Sahara have to promote sustainable development processes through foreign trade? And what support would the European Union and United States be able to offer? (SWP Comments)
Keywords: 320